1991
DOI: 10.1002/j.1460-2075.1991.tb07811.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of cDNA clones for plant cyclins.

Abstract: We have isolated and sequenced a carrot cDNA and two soybean cDNAs encoding mitotic cyclin homologs. The soybean clones were derived from nearly identical cognate genes. The carrot cyclin and soybean cyclins were slightly more similar to A‐type and B‐type cyclins thus far defined, respectively. However, they had divergent amino acid sequences in the portion that is most highly conserved in known cyclins and we could not easily include them in either of the phylogenetic types. Since the homology between carrot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
1
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(99 citation statements)
references
References 45 publications
2
95
1
1
Order By: Relevance
“…The second highest similarity is to the alfalfa cyclin cycMs2 (Hirt et aL, 1992), with amino acid identities of 69.6 and 68.4% for cycOsl and cycOs2, respectively. Homologies to cyclins from Arabidopsis (Hemerly et al, 1992) and soybean (Hata et aL, 1991) (Minshull eta/., 1990;Hunt, 1987, 1989), is FMRRFLK in both cycOsl and cycOs2. Both clones are too short at the 5' end to include a mitotic destruction box.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second highest similarity is to the alfalfa cyclin cycMs2 (Hirt et aL, 1992), with amino acid identities of 69.6 and 68.4% for cycOsl and cycOs2, respectively. Homologies to cyclins from Arabidopsis (Hemerly et al, 1992) and soybean (Hata et aL, 1991) (Minshull eta/., 1990;Hunt, 1987, 1989), is FMRRFLK in both cycOsl and cycOs2. Both clones are too short at the 5' end to include a mitotic destruction box.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of two highly conserved regions in the 'cyclin box' of plant cyclins (Hata et aL, 1991;Hemerly et aL, 1992;Hirt et aL, 1992;Renaudin et aL, 1994) two degenerate primers were derived.…”
Section: Isolation Of Rice Cyclin Cdna Clonesmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy was successful for isolating theArabidopsis 3-hydroxy-3-methylglutaryl-CoA reductase gene (21,22). The mouse squalene synthase cDNA (11) was used as a probe, because we had found that plant cell-cycle-related genes were more similar to mammalian homologs than to yeast homologs (23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Poly (A)-rich RNA was isolated from a mixture of staged embryos (globular stage/heart stage/torpedo stage = 1 :2:4, fresh mass). The construction of a AZAPII cDNA library has already been described [15]. Genomic DNA was prepared [17] from a cell line, named IM-1, which was obtained from the above suspen-…”
mentioning
confidence: 99%